Artemisinin Efficacy on iNOS Production in U937 Cell-line Infected with Leishmania donovani - Neamah, Suhair Dakhil; Ali, Hayder Z.; Al-Halbosiy, Mohammad M.F. (Iraqi Journal of Science, 2023)
Visceral leishmaniasis (VL), the second-most-serious parasitic illness after malaria, is currently endemic in more than 88 countries. Need for new anti-leishmanial compounds is currently being taken into consideration by researchers due to resistance and lack of effective vaccinations. This research was conducted to find out more about the effect of artemisinin (ART). ART was examined in vitro promastigotes stages and ex vivo amastigotes stages of the Iraqi strain of Leishmania donovani in U937 cell line after 24, 48 and 27 hours using MTT assay. In addition, the level of macrophage nitric oxide (NO) was measured using Griess assay in U937 cell line. The results of promastigotes viability percentage were less than 50 %, where the IC50 was 43.8, 37.9 and 36.6 µM respectively. Similar cytotoxic effect of ART was observed against amastigote forms, where the cell viability was 36.11, 40.2 and 37.4 µM respectively, after the three times of follow up.. Furthermore, by using Griess assay the level of nitrite in infected macrophages was measured. The results after 48hr were 6.58 in high concentration and 1.22 in lower concentration. However, considering the absence of a significant difference, the observed concentrations are still higher than the control when compared to Griess assay.. These findings demonstrated that ART has a cytotoxic effect on both forms of L. donovani. It also increased iNOS production in infected macrophages which can define artemisinin therapeutic efficacy against L. donovani infection.